New insights in the metabolism of oxybutynin: evidence of N-oxidation of propargylamine moiety and rearrangement to enaminoketone. (4th May 2018) - Aprile, Silvio; Canavesi, Rossana; Matucci, Rosanna; Bellucci, Cristina; Del Grosso, Erika; Grosa, Giorgio
Abstract: 1. Oxybutynin hydrochloride is an antimuscarinic agent prescribed to patients with an overactive bladder (OAB) and symptoms of urinary urge incontinence. Oxybutynin undergoes pre-systemic metabolism, and the N -desethyloxybutynin (Oxy-DE), is reported to have similar anticholinergic effects. 2. We revisited the oxidative metabolic fate of oxybutynin by liquid chromatography–tandem mass spectrometry analysis of incubations with rat and human liver fractions, and by measuring plasma and urine samples collected after oral administration of oxybutynin in rats. This investigation highlighted that not only N -deethylation but also N -oxidation participates in the clearance of oxybutynin after oral administration. 3. A new metabolic scheme for oxybutynin was delineated, identifying three distinct oxidative metabolic pathways: N -deethylation (Oxy-DE) followed by the oxidation of the secondary amine function to form the hydroxylamine (Oxy-HA), N -oxidation (Oxy-NO) followed by rearrangement of the tertiary propargylamine N -oxide moiety (Oxy-EK), and hydroxylation on the cyclohexyl ring. 4. The functional activity of Oxy-EK was investigated on the muscarinic receptors (M1-3 ) demonstrating its lack of antimuscarinic activity. 5. Despite the presence of the α, β -unsaturated function, Oxy-EK does not react with glutathione indicating that in the clearance of oxybutynin no reactive and potentially toxic metabolites were formed.